Postoperative parenteral glutamine supplementation improves the short-term outcomes in patients undergoing colorectal cancer surgery: A propensity score matching study - Tang, Gang; Pi, Feng; Qiu, Yu-Hao; Wei, Zheng-Qiang (Frontiers in Nutrition, 2023)
The clinical utility of glutamine in patients undergoing colorectal cancer (CRC) surgery remains unclear. Therefore, we aimed to investigate the impact of postoperative treatment with glutamine on postoperative outcomes in patients undergoing CRC surgery. We included patients with CRC undergoing elective surgery between January 2014 and January 2021. Patients were divided into the glutamine and control groups. We retrospectively analyzed postoperative infections complications within 30 days and other outcomes using propensity score matching and performed between-group comparisons. We included 1004 patients who underwent CRC surgeries; among them, 660 received parenteral glutamine supplementation. After matching, there were 342 patients in each group. The overall incidence of postoperative complications was 14.9% and 36.8% in the glutamine and control groups, respectively, indicating that glutamine significantly reduced the incidence of postoperative complications (P < 0.001; risk ratio [RR] 0.41 [95% CI 0.30-0.54]). Compared with the control group, the glutamine group had a significantly lower postoperative infection complications rate (10.5% vs. 28.9%; P < 0.001; RR 0.36 [95% CI 0.26-0.52]). Although there was no significant between-group difference in the time to first fluid diet (P = 0.052), the time to first defecation (P < 0.001), first exhaust (P < 0.001), and first solid diet (P < 0.001), as well as hospital stay (P < 0.001) were significantly shorter in the glutamine group than in the control group. Furthermore, glutamine supplementation significantly reduced the incidence of postoperative intestinal obstruction (P = 0.046). Moreover, glutamine supplementation alleviated the decrease in albumin (P < 0.001), total protein (P < 0.001), and prealbumin levels (P < 0.001). Taken together, postoperative parenteral glutamine supplementation can effectively reduce the incidence of postoperative complications, promote the recovery of intestinal function, and improve albumin levels in patients undergoing CRC surgery.